DRYING OF EMPTY FRUIT BUNCHES AS WASTED BIOMASS BY HYBRID SOLAR–THERMAL DRYING TECHNIQUE - H. H. Al-Kayiem; Y. Md Yunus (Journal of Mechanical Engineering and Sciences, 2013)
Solar drying of EFB is highly feasible and economic, but the solar drying process is interrupted during cloudy or rainy days and also at night. In the present paper, a combined solar, as the main heat input, and biomass burner, as an auxiliary source of thermal energy, has been investigated experimentally to dry EFB. An experimental model consisting of a solar dryer integrated with a thermal backup unit was designed and fabricated. A series of experimental measurements were carried out in four different drying modes, namely, open sun, mixed direct and indirect solar, thermal backup, and hybrid. The results from the four modes used to dry 2.5 kg of EFB were summarized and compared. The results indicated that the solar drying mode required around 52 to 80 hours to dry the EFB, while the open sun drying mode required 100 hours. Usage of the thermal backup as heat source reduced the drying time to 48–56 hours. With the hybrid mode, the drying time was considerably reduced to 24–32 hours. The results demonstrate that the combined solar and thermal backup effectively enhanced the drying performance. The application of a solar dryer with a biomass burner is practical for massive production of solid fuels from EFB.